Sistem Kontrol Temperatur Metode Pid Heatbed dan Ekstruder pada Printer Tiga Dimensi - Aidil Alfajri; Mukhlidi Muskhir (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Control of the temperature on the Hotend and HeatBed is very important. An inaccurate and unstable temperature on the extruder can disrupt the extrusion process which results in a lack of quality printouts. The purpose of this research is to create a temperature control system for Hotend and Heat Bed using the PID (Proportional Integral Derivative) method which is applied to three-dimensional printers using the FDM and PLA Filament methods. The control system uses two separate PID systems on the Hotend and Heat Bed but still uses the same microcontroller. On the Hotend, the PID data input is obtained from a 100k Ohm Thermistor which is connected to the Microcontroller analog pin via a 3-dimensional printer shield. The output is a PWM signal from the microcontroller to the heating element via a MOSFET which will later be attached to the hotel. Based on the tests that have been carried out, the temperature control system using the PID method can control the temperature at the hotend with an error rate of 0.5% and there is no error or overshoot at the heatbed temperature.